The Prevalence of Refractive Errors in Elementary School Children at SDN 16 and 17 Duri Kepa, West Jakarta, 2023/2024: Prevalensi Kelainan Refraksi Mata Pada Anak Usia Sekolah Dasar di SDN 16 dan 17 Duri Kepa Jakarta Barat 2023/2024 - Da Costa, Sandra Aparasiba; Silaen, Desi Hartati; Farfar, Inggrid Osya (Jurnal MedScientiae, 2025)
Refractive eye disorders are common among elementary school-age children and can affect their quality of life and academic performance. The World Health Organization (WHO) reports that approximately 153 million people experience vision impairment due to uncorrected refractive errors, with 70% of blindness in Indonesia caused by this issue. Children with uncorrected refractive errors often struggle to read the blackboard, see learning materials, and experience headaches and eye fatigue. This study aims to determine the prevalence and types of refractive errors in students of SDN 16 and 17 Duri Kepa, West Jakarta.  A quantitative cross-sectional study design was used, with examinations conducted using the Snellen Chart and autorefractometer to measure students' visual acuity.  Of 601 students, 309 (51.4%) had refractive errors. The most common type of refractive error was a combination of myopia and astigmatism (47.6%). The distribution by gender showed that more females (55.8%) had refractive errors than males (50.7%). The highest prevalence was found in 8-year-old children (21.1%) and 2nd-grade students (26.6%). The importance of routine eye examinations in elementary schools to detect refractive errors early and raise awareness about eye health.